Innovations for Increasing Awareness of Sexual and Gender-Related Violence - Innocent Besigye; Anna Kabona; Brenda Tusubira (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2026)
Sexual and gender-related violence against girls and women (SGRV) has been described as “a dark stain on the fabric of life” and is rightly regarded as the most pervasive breach of human rights. While the incidence of SGRV documented by individual countries varies, the overall prevalence is unacceptably high as 1 in 3 women worldwide report suffering gender-based violence in their lifetime. Consequently, all healthcare providers and educators have a responsibility to include gender respect in the care they provide, and to raise awareness of the burden of gender-related violence in their health promotion. The World Health Organization (WHO) and United Nations International Children’s Fund (UNICEF) continue to call for novel approaches to increase awareness of SGRV globally, empower societies and reduce the burden of gender-related violence; the United Nations (UN) sustainable development goals also include SGRV as a target for change. The literature now includes evidence of the value of several innovative approaches that use culturally-based initiatives and the impact of music and song. These forms of health promotion are examples that we as global health providers can employ. They have particular relevance where initiatives are aimed at engaging young people and for programs delivered in a school setting, but older folk can contribute through folk tales and traditional dramas, as these continue to provide a rich foundation for traditional communication on intricate topics. We all have a responsibility to do more to counter SGRV; ideally in so doing this will contribute further to the innovative evidence-based approaches WHO, UNICEF and the UN continue to call for.